Trauma Yang di Alami Anak Binaan Pelaku Pembunuhan di Lpka Kelas II Tomohon - Gigir, Yosua; Kumois, Ananda; Ariestyawan, I Made Devastha (Jurnal Ilmiah Wahana Pendidikan, 2024)
The crime of premeditated murder committed by teenagers does not just happen. There is a psychological process that plays a role in the murder. This research aims to describe the phenomenon of planned murder crimes committed by teenagers who are leaders at the Tomohon Child Special Development Institute (LPKA) class II. The subject is a teenage comedian who committed the crime of premeditated murder in Tomohon. The approach in this research is qualitative with a case study method. Data collection techniques use interviews and observation. The research results illustrate that the psychological mechanisms that occur in the phenomenon of murder committed by teenagers consist of two main factors, namely internal and external factors. Internal factors include personality, thinking ability, and emotional condition. Meanwhile, external factors include the social environment, level of education, and stimulus from the victim himself.